Global Fiscal Adjustment and Trade Rebalancing : Global Fiscal Adjustment and Trade Rebalancing - McKibbin, Warwick J. (World Bank, Washington, DC, 2012)
The emergence of substantial fiscal deficits and a large build up of government debt in major advanced economies will inevitably lead to a period of fiscal consolidation in coming years. In an earlier paper, McKibbin and Stoeckel (2010) explored the effects of this fiscal adjustment in advanced economies on the global economic outlook. This paper focuses on the differences between the impacts of fiscal policy in advanced versus emerging economies. In particular, the need for more fiscal spending on infrastructure in emerging economies and the need for fiscal consolidation in advanced economies leads naturally to the question of what this asymmetric fiscal adjustment might do to global trade balances as well as global economic growth over the coming decades. The adjustment needed in both regions is substantial and the asymmetry of the adjustment implies important consequences for trade and capital flows between regions as well as asset price adjustments within and between regions.